Earlier colony arrival but no trend in hatching timing in two congeneric seabirds (Uria spp.) across the North Atlantic - Merkel, Benjamin; Descamps, Sebastien; Yoccoz, Nigel Gilles; Danielsen, Jóhannis; Daunt, Francis; Erikstad, Kjell E; Ezhov, Aleksey V.; Grémillet, David; Gavrilo, Maria; Lorentsen, Svein Håkon; Reiertsen, Tone Kristin; Steen, Harald; et al. (Biology Letters, 2019)
Accepted manuscript. Final version published in Biology Letters, 15 (10), is available at https://doi.org/10.1098/rsbl.2019.0634. A global analysis recently showed that seabird breeding phenology (as the timing of egg-laying and hatching) does not, on average, respond to temperature changes or advance with time (Keogan et al. 2018 Nat. Clim. Change 8 , 313–318). This group, the most threatened of all birds, is therefore prone to spatio-temporal mismatches with their food resources. Yet, other aspects of the breeding phenology may also have a marked influence on breeding success, such as the arrival date of adults at the breeding site following winter migration. Here, we used a large tracking dataset of two congeneric seabirds breeding in 14 colonies across 18° latitudes, to show that arrival date at the colony was highly variable between colonies and species (ranging 80 days) and advanced 1.4 days/year while timing of egg-laying remained unchanged, resulting in an increasing pre-laying duration between 2009 and 2018. Thus, we demonstrate that potentially not all components of seabird breeding phenology are insensitive to changing environmental conditions.